Relationship between surgeon experience and adverse events in thyroid surgery - Loderer, Tommaso; Beretta, Davide; Cozzani, Federico; Bonati, Elena; Rossini, Matteo; Del Rio, Paolo (Acta Biomedica Atenei Parmensis, 2021)
In scientific literature there are numerous authors that have highlighted how the outcome of patients undergoing surgical treatment, such as intraoperative or postoperative complications, surgical time, mean hospital stay, is related to the surgeon’s experience based on the number of cases treated per year for a specific disease. In our study we decided to verify if, in our clinical practice, there are significant differences in postoperative outcomes between procedures performed by a senior surgeon, a young specialist or a surgical resident, evaluating if surgical experience affects positively either on intraoperative complications such as bleeding, hypocalcemia, dysphonia, or on surgical time, mean hospital stay and postoperative complications. In this retrospective study we examined all cases of patients that underwent surgery for thyroid disease at our Operative Unit, from January 1, 2015 to December 31, 2019. The analysis of our data highlights how the surgeon’s experience affects the surgical outcome of patients undergoing lobectomy or total thyroidectomy. Our conclusion was that a high volume center, like the one we are working in, with a correct selection of the patients, allows to train a surgical resident guaranteeing both the surgical training of the doctor and the patients safety.